INDEKS KEBERLANJUTAN USAHATANI PADI DI TASIKMALAYA - Maryono Maryono (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2018)
The global agenda, namely sustainable development goals (SDGs), requires all businesses activities including farming to carry out a process of production that concerns on its sustainability. This study examined the extent to which of the sustainability level of rice farming in a multidimensional perspective from the three pillars of sustainability, namely economic, social, and environmental. Tasikmalaya District was purposively chosen because there was so called environmentally friendly farmer organization applying system of rice intensification (SRI) method. As much as sixty farmers were selected randomly as respondents. The analytical method used in this study refers to the Composite Index developed by OECD (2013) by comparing the index score of its pillars. The results indicate that the sustainability index of rice farming is of 0.46. The environmental dimension contributes the highest score to the total index that indicate very good performance, however, still lacking in the social and economic dimension. Therefore it is necessary to strengthen the last two pillars so that all the three pillars of sustainability can be achieved rateably.